Pertanggungjawaban Pembayaran Royalti Konser Perspektif Fatwa MUI Nomor 1 Tahun 2003 tentang Hak Cipta - Turnip, Devi Cantika; Yazid, Imam (AL-SULTHANIYAH, 2025)
Royalty payments for the use of musical works often raise legal issues, par-ticularly regarding the parties responsible in commercial concerts. This study aims to analyze the licensing mechanism for the use of copyrighted works under Law No. 28 of 2014, identify the parties responsible for paying royalties in concerts, and examine these obligations from an Islamic legal perspective as interpreted by the Indonesian Ulema Council (MUI). The re-search method used is normative legal research with a legislative and con-ceptual approach. The results of the study show inconsistencies between Ar-ticle 9 paragraphs (2)-(3) and Article 23 paragraph (5) of the Copyright Law, which create legal uncertainty regarding the licensing mechanism for the use of copyrighted works. In commercial concerts, the EO is designated as the party most responsible for royalty payments because it manages all as-pects of the event and derives economic benefits. From an Islamic legal per-spective, copyright falls under ḥuqūq māliyyah, which must be protected, and violations of it are categorized as ẓulm. Therefore, royalty payments are a religious obligation to uphold the principles of justice and protection of property rights in transactions.